Narrativas e cidades: uma cartografia de paisagens possíveis para o jornalismo - Peres, Ana Claudia Mendes de Andrade e (2012)
The city is a place of encounters. To narrate it, journalism often appropriates raw facts and statistics. However, there are in this field, many ways to portrait the urban experience in stories that go beyond technical rationality. This dissertation is an attempt to understand the journalistic narratives as producers of meaning as well as the city as a text, proposed by Michel de Certeau. Therefore, it takes the narratives about the cities in piauí Magazine as a starting point for investigating the discursive strategies that, by combining the real and the poetic, amplify the fact. To these texts, it is juxtaposed other ones found in contemporary vehicles as part of an effort to map narratives that, in their own weaving, produce dialogues and relate subjects. In the process of analysis of these narratives, it emerges enunciative clues leading to a map of other landscapes to the cities and to contemporary journalism